Bamboo residue as a potential activated carbon for removal of water pollutants: a commentary. (3rd April 2022) - Supee, Aiman Hakim; Zaini, Muhammad Abbas Ahmad
ABSTRACT: Bamboo is one of the fastest-growing plants that exist on earth and can be found in many countries. Its application generally ranges across both the engineering and non-engineering sectors. Traditionally, bamboo is mainly used in the construction field, but recent trends and studies have also shown its potential in the water treatment industry as a low-cost adsorbent. Thus, this paper aims to highlight the recent studies on bamboo residue as a potential precursor for activated carbon as well as its performance in treating water pollutants. Apart from that, the current limitations, and suggestions on the further development of bamboo activated carbon, are also integrated to provide insight on its potential usage in the industrial process.